Atividade e estado de fosforilação da Na+,K+-ATPase nas convulsões induzidas por pentilenotetrazol em camundongos - Marquezan, Bárbara Picada (2012)
In the brain, Na+,K+-ATPase activity is essential for maintaining of the electrochemical gradient underlying the resting potential and release and uptake of neurotransmitters, and a decrease in its activity alters brain excitability. Recent studies show that mutations in the gene encoding the Na+,K+- ATPase alpha subunit containing residues of phosphorylation Serine 943 and Tyrosine 10 cause the appearance of seizures, and that ouabain, a Na+,K+-ATPase inhibitor, causes seizures in mice. Given this association between Na+,K+-ATPase and seizures, and the large number of epilepsy affected individuals which are refractory to current antiepileptic drugs available, the aim of this study was to determine whether a correlation exists between Na+,K+-ATPase activity and subunit expression and phosphorylation state and induction of the seizures induced by pentylenetetrazol (PTZ), a classic convulsant agent. Adult male Swiss mice treated with PTZ (30, 45 or 60 mg/kg, i.p.) caused convulsions in a dose-dependent manner and administration of PTZ (60 mg/kg) decreased Na+,K+- ATPase activity by 37.63 % in the cerebral cortex but not in the hippocampus. We detected a positive correlation between activity Na+,K+-ATPase in the cerebral cortex and the latency for clonic seizures (r²=0.55, P<0.05) and generalized seizures (r²=0.61, P<0.05). Collectively, these data indicate a relationship between decreased activity Na+,K+-ATPase and onset of convulsions induced by PTZ (60 mg/kg). There was no change in Na+,K+-ATPase protein expression in cerebral cortex after seizures induced by PTZ (60 mg/kg). This fact together with the lack of correlation between subunit expression and latency to clonic seizure and generalized seizure suggest decreased in Na+,K+- ATPase activity in the mice cerebral cortex after PTZ (60 mg/kg) didn’t is due to change in protein expression. Furthermore, we find an increase in subunit Ser943 and Tyr10 residues phosphorylation after seizures induced by PTZ (60 mg/kg) and also found a negative correlation between Ser943 phosphorylation and latency for generalized convulsion. We conclude that there is a close relationship between the decrease in Na+,K+-ATPase activity in the parietal cortex of mice and the onset of PTZinduced generalized seizures and decreased activity Na+,K+-ATPase is not related to changes in protein expression, but to phosphorylation of Ser943 and Tyr10 residues.